Airway reconstruction using decellularized aortic xenografts in a dog model. (2nd July 2020) - Cheng, Shao-Fei; Wu, Song; Li, Qian-Ping; Sang, Hong-Yang; Fan, Zheng-Yang
ABSTRACT: Tracheal reconstruction after extensive resection remains a challenge in thoracic surgery. Aortic allograft has been proposed to be a potential tracheal substitute. However, clinically, its application is limited for the shortage of autologous aortic segment. Whether xenogeneic aortic biosheets can be used as tracheal substitutes remains unknown. In the present study, we investigated the possibility in dog model. The results show that all dogs were survived without airway symptoms at 6 months after tracheal reconstruction with gently decellularized bovine carotid arteries. In the interior of engrafted areas, grafted patch integrated tightly with the residual native tracheal tissues and tracheal defects in the lumen were repaired smoothly without obvious inflammation, granulation, anastomotic leakage, or stenosis. In addition, histological and scanning electron microscopy examination showed that grafted patches were covered with ciliated columnar epithelium similar to epithelium in native trachea, which indicated successfully re-epithelialization of decellularized bovine carotid arteries in dogs. These findings provide preclinical investigation of xenogeneic aortic biosheets in serving as tracheal substitute in a dog model, which proposes that decellularized biosheets of bovine carotid may be a potential material for bioartificial tracheal graft.